Brief Review of Methods to Quantify High-Speed Running in Rugby League: Are Current Methods Appropriate?. Issue 3 (11th June 2022) - Bennett, Thomas; Marshall, Phil; Barrett, Steve; Malone, James J.; Towlson, Chris
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: High-speed running (HSR) has been documented within rugby league to differentiate playing standard and position and often precedes pivotal match events. Practitioners and researchers place importance on HSR because of its inclusion in assessing the demands of training and match play to help prescribe accurate training loads and recovery methods. HSR can be quantified in absolute terms whereby the same threshold speed is applied to all players (e.g., 5.0 m·s −1 ). Within rugby league, differences in tactical demand, anthropometric, and physical fitness characteristics exist between positions and players, suggesting that absolute HSR thresholds may not be appropriate because of underestimations and overestimations of HSR data. Alternatively, practitioners may individualize the threshold speed to individual players' physical qualities such as peak sprint speed, maximal aerobic speed (MAS), or the speed at which the ventilatory thresholds occur. Individualizing HSR warrants the practitioner to select a valid and practical test to quantify the HSR threshold speed. It is suggested that using peak sprint speed to quantify HSR can produce erroneous interpretation of HSR data while the practicality of specific physiological derived thresholds can be questioned. Implementing MAS to quantify HSR using a set time/distance trial may be the most appropriate approach for rugby league practitioners.